Stability of non-precious metal in corrosive electrolyte - Pang, Loo Ping (Nanyang Technological University, 2023)
Aluminium has been heavily investigated in recent years as electrodes in rechargeable metal batteries, due to their large capacity and energy density, as well as their high abundance in nature. However, the instability of aluminum in a corrosive electrolyte environment due to the loss of Al metal during charge and discharge remains a challenge for the stability and rechargeability of the battery. As a result, liquid cell transmission electron microscopy (LCTEM) was used to investigate the degradation behavior of the Aluminium in the corrosive electrolyte. A thin Al film was deposited onto an electrochemical chip, and Al2(SO4)3 electrolyte was used as it may be a source of Al ions to replenish the consumed Al metal. The morphology and composition of the Al film were then investigated using various characterization tools.